Penyuluhan Kesehatan Bahaya HIV dan AIDS Dan Pencegahannya di SMA Santa Maria Pekanbaru - Prima Octafia Damhuri (CV. Multi Kreasi Media, 2022)
HIV and AIDS is one of the dangerous diseases that cannot be cured. Based on data from the Riau Health Office, the number of HIV cases in 2019 was 533 cases. The number of HIV cases in the 15-19- year-old was 7 cases, the 20-24-year-old was 77 cases and the highest was found in the 25-49-year-old was 397 cases. This was the basis of the author's interest in conducting counseling about HIV and AIDS at Santa Maria High School Pekanbaru. This counseling aims to provide information and understanding about HIV and AIDS. The method used was counseling by delivering information through lectures and conducting questions and answers to the community to increase understanding and awareness about HIV and AIDS. This counseling would be held on April 5, 2022 at 09.00 WIB to 11.00 WIB at Santa Maria High School Pekanbaru. The result of this counseling was the implementation of counseling about HIV and AIDS to Santa Maria High School Pekanbaru students by providing information and understanding about the importance of a healthy lifestyle to prevent people from contracting HIV and AIDS.